Compétences transversales : quelques suggestions pour s’affranchir d’un mythe - Jean-Claude Coulet (Recherches en Éducation)
Starting from the reasons explaining the interest in transversal competencies, we will show that the difficulties encountered in their use, above all, stem from the lack of reference to a theoretical model of individual and collective competencies. With reference to the theories of activity, we will try therefore to present the contributions of such a model. That will be illustrated through some examples of the operationalization of this theoretical framework in the field of education and training as well as within organizations and territories.